Digital teaching as the new normal? Swedish upper secondary teachers' experiences of emergency remote teaching during the COVID-19 crisis. (July 2021) - Nilsberth, Marie; Liljekvist, Yvonne; Olin-Scheller, Christina; Samuelsson, Johan; Hallquist, Claes
This paper takes an interest in how schools and teachers dealt with new demands when teaching rapidly went online during school closures related to the COVID-19 pandemic, in what we see as an example of emergency remote teaching. The aim is to make visible how schools and teachers dealt with the demands that they were confronted with while under hard pressure during emergency remote teaching, and what discursive frames are used in upper secondary teachers' pedagogical considerations. Fifteen teachers of history, mathematics and Swedish (five from each subject) are followed in recurring interviews between April 2020 and September 2020, resulting in a total of 41 interviews. A narrative approach is used in the analysis and results show how teachers made large efforts to maintain teaching in what can be described as a crisis organization. Three main discourses are identified: (a) a strong assessment discourse; (b) a relational discourse; and (c) a compensatory discourse. The findings are discussed in the light of educational policy based on the so-called Nordic model and the idea of one-school-for all, and in relation to what becomes possible to teach as well as what is not possible to do in times of crisis.